(untitled) (Annual of the Faculty of Philosophy in Skopje, 2017)
The form a-te-wo-jo occurs once on the Pylos tablet Sa 797. Although there aren’t other forms, neither in nominative, nor in any other case, to be compared with a- te-wo-jo, still the analysis of the intermediate context of the particular tablet and the analysis of the Sa series in general, allows us to conclude that this is a personal name in genitive, ending in -oio. Although, because of the polysemantic value of the Mycenaean syllabograms different interpretations are possible, still the comparison with other personal names in Mycenaean and in Post-Mycenaean Greek, allows us to interpret the personal name *a-te-wo as a hypocoristic of a compound personal name composed of άνθέω, “bloom, flourish, be brilliant, shine ”, as first element and οίνος, “wine ”, as second element.